2021
DOI: 10.1136/bmjopen-2020-041604
|View full text |Cite
|
Sign up to set email alerts
|

Identifying co-occurrence and clustering of chronic diseases using latent class analysis: cross-sectional findings from SAGE South Africa Wave 2

Abstract: ObjectivesTo classify South African adults with chronic health conditions for multimorbidity (MM) risk, and to determine sociodemographic, anthropometric and behavioural factors associated with identified patterns of MM, using data from the WHO’s Study on global AGEing and adult health South Africa Wave 2.DesignNationally representative (for ≥50-year-old adults) cross-sectional study.SettingAdults in South Africa between 2014 and 2015.Participants1967 individuals (men: 623 and women: 1344) aged ≥45 years for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…The comorbidity clusters identi ed in our study are similar to those in previous studies (39,40). A systematic review of comorbidity patterns from 39 studies conducted in 12 countries identi ed hypertension and arthritis as the most frequent comorbidity combination (40).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The comorbidity clusters identi ed in our study are similar to those in previous studies (39,40). A systematic review of comorbidity patterns from 39 studies conducted in 12 countries identi ed hypertension and arthritis as the most frequent comorbidity combination (40).…”
Section: Discussionsupporting
confidence: 86%
“…A systematic review of comorbidity patterns from 39 studies conducted in 12 countries identi ed hypertension and arthritis as the most frequent comorbidity combination (40). Another study conducted in South Africa found two distinct comorbidity clusters comprising hypertension and diabetes and cardiopulmonary diseases such as angina, asthma and chronic lung disease (39). In our study, 72.3% of the participants were classi ed under minimal comorbidity, 18.9% under hypertension and arthritis class and 8.9% under cardiopulmonary class.…”
Section: Discussionmentioning
confidence: 44%
“…The largest disease class in our study was "Diabetes and Hypertension." This combination of diseases has been previously identified in the literature both regionally [53][54][55][56] and internationally [57]. A multi-country study based in sub-Saharan Africa found that hypertension was the most common co-morbidity in a cohort of diabetes patients and was present in approximately 71% of patients with diabetes [58].…”
Section: Discussionmentioning
confidence: 58%
“…depression, cognitive impairment, edentulism and obesity as a disease condition) and therefore reported higher prevalence of multimorbidity. A recent analysis of Wave 2 SAGE (2014/2015) [ 47 ] of adults aged 45 years and older, included fewer disease conditions than Garin et al . [ 20 ] (7 vs. 12); reported a multimorbidity prevalence of 21%.…”
Section: Discussionmentioning
confidence: 99%